Penerapan Seven Tools dalam Meningkatkan Kualitas Produk di Konveksi PT Tunggal Putri Rahayu Bandung - Saffana, Saudah Putri; Herdian, Faldy (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The high number of defects in convection products is one of the main problems that have an impact on reducing quality and consumer confidence. The purpose of this research is to identify the dominant types of defects, trace the main causes, and design improvement proposals based on Seven Tools as a quality control method. The method used in this research is a quantitative descriptive approach by collecting defective product data from January to December 2024. The data was analyzed using Check Sheet, Histogram, Pareto Diagram, Fishbone Diagram, Scatter Diagram, Control Chart, and Flowchart tools to trace the patterns, causes, and stability of the production process. The results show that the most common types of defects are loose buttons and broken threads, which are influenced by human factors, machines, work methods, and materials. After the implementation of improvement proposals, such as labor training, the use of semi-automatic machines, and the arrangement of the work environment, the product defect rate has decreased significantly. Thus, Seven tools proved effective in analyzing quality problems and became a solution to improve the quality of convection production.